(untitled) (OODBODHAN, 2026)
This paper explores vibration-based structural health monitoring (SHM) for the reinforced concrete (RCC) T-beam bridge over Nakhu Khola in Kathmandu Valley, Lalitpur, Nepal, using smartphone accelerometers for data collection. Short-term ambient vibration data is analyzed using Operational Modal Analysis (OMA) methods including Peak Picking (PP), Frequency Domain Decomposition (FDD), Enhanced Frequency Domain Decomposition (EFDD), and Stochastic Subspace Identification (SSI) in MATLAB. A Finite Element Modal (FEM) is developed in CSI Bridge for validation through modal frequency and Mode shape comparison. Results indicate that smartphone sensors effectively capture first three vertical bending frequency with discrepancies from FEM 15% and modal assurance criteria for first three vertical bending mode greater than 0.95. Damage is simulated by reducing stiffness 30% at selected mid longitudinal girder elements that represent structural deterioration. The results showed that stiffness reduction caused a decrease in natural frequencies. The first vertical bending mode was found to be the most sensitive to damage. This low-cost approach is suitable for short-term SHM in seismically active regions like Nepal, facilitating rapid assessments post-events such as floods or earthquakes.